2020
DOI: 10.3917/ls.171.0171
|View full text |Cite
|
Sign up to set email alerts
|

Vous avez dit FALC ? Pour une adaptation linguistique des textes destinés aux migrants nouvellement arrivés

Abstract: Cet article interroge les principes de simplification recommandés par le FALC (« Facile à Lire et à Comprendre »), qui font partie des ressources utilisées par les acteurs socio-éducatifs pour la rédaction de textes informatifs à destination des migrants nouvellement arrivés et peu ou pas francophones. À partir de l’étude de documents écrits « simplifiés » destinés à des mineurs étrangers isolés (MNA), nous mettons en évidence la persistance de difficultés linguistiques qui peuvent entraver la compréhension et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…stance, despite their intact structural language competence, individuals with Asperger syndrome and more broadly those with autism spectrum disorder are known to experience significant challenges understanding figurative language (idioms) in their native language (Kalandadze et al, 2018). It is also widely acknowledged that idiomatic expressions are some of the hardest aspects of language acquisition and processing for second language learners (Liontas, 2002;Ellis et al, 2008;Canut et al, 2020). Moreover, natural language processing systems are known to be negatively impacted by idioms in text ( (Salton et al, 2014;Shao et al;Shutova et al, 2013) shown the negative impact of idioms and metaphors on machine translation leading to awkward or incorrect translations from English to other languages).…”
Section: Bartmentioning
confidence: 99%
“…stance, despite their intact structural language competence, individuals with Asperger syndrome and more broadly those with autism spectrum disorder are known to experience significant challenges understanding figurative language (idioms) in their native language (Kalandadze et al, 2018). It is also widely acknowledged that idiomatic expressions are some of the hardest aspects of language acquisition and processing for second language learners (Liontas, 2002;Ellis et al, 2008;Canut et al, 2020). Moreover, natural language processing systems are known to be negatively impacted by idioms in text ( (Salton et al, 2014;Shao et al;Shutova et al, 2013) shown the negative impact of idioms and metaphors on machine translation leading to awkward or incorrect translations from English to other languages).…”
Section: Bartmentioning
confidence: 99%
“…stance, despite their intact structural language competence, individuals with Asperger syndrome and more broadly those with autism spectrum disorder are known to experience significant challenges understanding figurative language (idioms) in their native language (Kalandadze et al, 2018). It is also widely acknowledged that idiomatic expressions are some of the hardest aspects of language acquisition and processing for second language learners (Liontas, 2002;Ellis et al, 2008;Canut et al, 2020). Moreover, natural language processing systems are known to be negatively impacted by idioms in text ( Shutova et al, 2013) shown the negative impact of idioms and metaphors on machine translation leading to awkward or incorrect translations from English to other languages).…”
Section: Bartmentioning
confidence: 99%